Letter (copy) : Largo Caballero and others - Tewson, Vincent
013-0067-001 International. HVT/WJB/DT/109. substitute 15th November, 1940. Mr. W. Carrillo, 7, Orme Court, LONDON, W.2. Dear Mr. Carrillo, LARGO CABALLERO AND OTHERS. We have duly received your letter of the 14th instant with regard to our old Comrade Largo Caballero and other leaders of the Spanish Trade Union Movement. We are very sorry indeed to learn of their grave position, and although our means for helping them are obviously limited to-day, we have taken measures which we hope will be helpful. Yours sincerely, Assistant Secretary. 292/946/13/67